Acute effects of resistance exercise with blood flow restriction on cardiovascular response: a meta-analysis - Lemos, Leonardo Kesrouani [UNESP] (2022)
Aim: To compare the acute effects of low-load resistance training associated with blood flow restriction (LLRT-BFR) with low-load resistance training (LLRT) and high-load resistance training (HLRT) on cardiovascular outcomes in healthy individuals. Methods: This review was registered and the studies were selected using seven databases. Randomized controlled clinical trials were included that evaluated LLRT-BFR compared with LLRT and HLRT in young individuals for the cardiovascular outcomes. Results: 19 studies were included. In the comparison of LLRT-BFR with HLRT, there were significant differences for cardiac output and heart rate - with reduced values and in favor of LLRT-BFR. Conclusion: There are no greater acute effects of the addition of blood flow restriction, with the exception of the reduction in cardiac output and heart rate for LLRT-BFR compared with HLRT.